Coercive, normative, and mimetic isomorphism inquiries on the crisis communication by hotels during the COVID-19 pandemic / Corina Joseph ... [et.al.]. - Joseph, Corina; Atlas, Ranee; Enggong, Tina Stephen; Rateh, Nicholas Rateh (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Crisis communication is essential during the pandemic. This paper aims to explain factors influencing crisis communication in three Sarawak-based hotels using the isomorphism tenet. A multiple case study approach was applied. A semi-structured interview with the hotel personnel was conducted in May 2022. It was found that the coercive isomorphism arises from the invitation by the state government for the two hotels to participate as the quarantine centers. In terms of mimetic isomorphism, hotels imitated the best practices of their peers in the same organizational field. Finally, normative isomorphism evidence was proven by professional networking via regular sharing of crisis information with staff and close relationships with parties that are responsible for addressing the pandemic issues, such as police, medical teams, hotel associations, hotel associates, and others. This research contributes to the crisis communication literature in the tourism industry particularly in an emerging economy in terms of promoting crisis disclosure on the website.